Laju Pertumbuhan dan Hasil Kubis Bunga Akibat Perlakuan Pupuk Organik Cair: Growth Rate and Yield of Cauliflower Due to Liquid Organic Fertilizer Treatment - Edy Kustiani; Supandji; Adib Adiana (Universitas Widya Gama Mahakam, 2021)
The people in Indonesia widely know cauliflower plants. In addition to their delicious taste, they also contain a high nutritional value for various kinds of dishes, both in restaurants and families. The purpose of this study was to determine the appropriate dose of liquid organic fertilizer (LOF) in order to obtain maximum growth and production of cauliflower (Brassica olerasea var Botritis). The study was conducted at the greenhouse of the Agriculture Faculty of Kadiri University. The experimental design employed a Completely Randomized Design (CRD), which consisted of six treatments repeated four times with a level test using the 5% Least Significant Difference test. Based on the results of observations and data analysis, it was found that the LOF dose treatment had no significant effect on the parameters of the average plant height, the number of leaves, and leaf area at the age of 9 days after planting (DAP). However, there was a highly significant difference in the observations of the average plant height, number of leaves and leaf area at the age of 16, 23 and 30 DAP. The average plant height, number of leaves, and leaf area were the largest in the D3 treatment (LOF dose of 75ml/plant). The observation of root wet-weight, root dry-weight, plant wet-weight, plant dry-weight, flower wet-weight, and flower dry-weight on different LOF dose treatment showed a highly significant difference, and the highest average was in the D3 treatment (75ml/plant). For the observation of harvest index, various doses of LOF showed a highly significant difference, and the highest average was in treatment D2 (50 ml/plant). However, it was not significantly different from D4 (100 ml/plant).